Exploring Unspoken Strength: The Power of Silence in August Strindberg’s The Stronger - Bhattarai, Rajendra (International Research Journal of MMC, 2025)
August Strindberg's one-act play The Stronger is an experimental work that explores the complex power dynamics between two women within an unconventional dramatic form, featuring only a single speaker. This research investigates the role of silence as a form of power in this play, and analyzes the psychological mechanisms through which silence undermines spoken authority. This article based on the qualitative research examines the paradoxical strength of silence. The study sheds light on Strindberg's innovative dramatic techniques, his nuanced portrayal of gender dynamics, and his deep psychological insight into human relationships. The play’s title itself poses a provocative and enduring question that fuels the dramatic tension: Who is truly “the stronger”—the woman who speaks or the woman who remains silent? Through a close analysis of the play’s structure, characterization, and psychological depth, this study argues that Strindberg’s use of silence serves not as a sign of weakness or subordination, but rather as a powerful and deliberate expression of strength, his study reveals the thematic and structural power of silence in Strindberg’s The Stronger, showing how it functions as a tool of psychological dominance and challenges the notion that speech equates to power. It also redefines silence in literary and gender contexts, emphasizing its role as a symbol of strength, autonomy, and dramatic innovation.